EVALUATION OF MEDICAL CHECK-UP (MCU) SERVICES WITH INFORMATION SYSTEMS AT PERMATA CIBUBUR HOSPITAL (Jurnal Indonesia Sosial Sains, 2025)
Evaluation of Medical Check Up (MCU) services with the implementation of information systems in hospitals is very important to identify the effectiveness and efficiency of the system used in the health services process. This study aims to evaluate various aspects of the implementation of information systems in MCU services, including the speed and efficiency of services, data integration, user satisfaction (patients and medical personnel), and the level of patient data security. The method used in this study is a qualitative approach with in-dept interview, direct observatio, and document analysis. Interview were conducted involving 30 informants, namely 4 general practitioners, 1 spesialist doctor, 5 health staff, 5 Medical Check Up nurses, 5 management, 5 administrative officer, and 5 participants who have undergone MCU. The results of the study indicate that the implementation of information systems in MCU serviceshas accelerated the administration process and increased the accuracy of patient data management. However, several technical obstacles, such as registration problems and suboptimal system integration., are still obstaclesin the implementation of services. In addition, although patients are satisfied with the ease of access to informationthrough the online portal, some of them feel that they do not fully understand the use ofthe system. Based on these findings, it is recommended to improve staff training, create integration between information systems with laboratories, radiology and strengthen the security of patient medical data. This research is expected to provide insight into development and improvement of information systems in MCU services in Permata Cibubur hospital to achieve more efficient, safe and quality services.